Growth curve of early-weaned Hereford calves in a semidesert temperate zone (Patagonia, Argentina) - Bruzzone, Octavio Augusto; Castillo, Daniel Alejandro; Villagra, Edgar Sebastian (Elsevier, 2022)
In semi desert environments, prone to droughts, beef cow performance can be improved by early weaning. This study aimed to evaluate the growth curve of early weaned calves in a semidesert temperate area such as Patagonia, Argentina, using a classical growth curve model. Hereford and crossbred (3/4 Hereford x 1/4 Aberdeen Angus) calves (n = 56), born in spring (September - November), from multiparous cows (4 to 8 years old), were weaned at 45–145 d of age, with 43–156 kg live weight and placed in a feedlot. After a period of adaptation, the calves were fed ad libitum with a diet of corn (48%), soybean expellers (12%) and alfalfa (40%), which was adjusted weekly for the previous week’s intake. The animals were weighed weekly. The growth curve was defined by a Bayesian stepwise model selection process based on Richards’ growth curve. The resulting model is a Gompertz-like curve (near-zero shape parameter), in which females experience a change in growth rate at about 62.7 kg, from where their r increases from 0.0065 to 0.0121 becoming similar to that of males. The whole model had a high fit, with a generalized r2 of 0.8782. The average daily gain (ADG) was 0.804 kg/day for female calves and 0.934 kg/day for male calves. Female calves weighing less than 80 kg had an ADG of 0.672 kg/day, and those weighing more had an ADG of 0.847 kg/day. The current growth curve shows that it is possible to achieve high ADG in early weaned calves, confirming that early weaning is a viable alternative to make production systems more efficient in semi desert environments like Patagonia. Knowing the relationship between concentrate feeds and livestock prices, farmers will be able to decide whether early weaning is a profitable alternative or not is a profitable alternative. However, special care must be taken when weaning heifers that weigh less than 80 kg to achieve high ADG.